Feldenkrais ‘Functional Integration’ Increases Body Contact Surface in the Supine Position: A Randomized-Controlled Experimental Study - Brummer, Matthias; Walach, Harald; Schmidt, Stefan (Frontiers in Psychology, 2018)
Feldenkrais ‘Functional Integration’ (FI) is a widely used type of body work with a focus on the continuous integration of body sensations and awareness with movement. The method is, amongst others, known for improving balance in aging populations, but also for its ability to relax muscles. With participants treated in the supine position FI is potentially changing the surface area of the body in contact with the surface on which a participant is lying. So far, no prior study has assessed this claim. We evaluated objectively and subjectively if a treatment with FI would induce changes in pressure and contact surface of the body on the mat. Thirty volunteers received an individual treatment with FI, in a randomized order on both sides of the body. Pressure and contact surface was documented with the Xsensor-Measurement-System. Subjective sensations were assessed with a self-report scale. Due to two parallel assessments alpha-level was adjusted to α = 0.025. We found that pressure and contact surface of the body on the mat significantly changed after the treatment (factor time: p < 0.0001, ηp2 = 0.90). We also found that pressure and contact surface increased significantly on the left side for the group that started with the left side first (time × group p = 0.016; ηp2 = 0.62), but less so on the right side for the group that started with the right side first (time × group: p = 0.056) although there was still a substantial effect size (ηp2 = 0.54). The subjective reports confirmed the physical measurements. In conclusion our results demonstrate for the first time that the treatment with the Feldenkrais method changes muscle tone leading to a more relaxed supine position with respect to pressure and contact surface on the mat.